Leaf litter dynamics in Agroforestry system affecting microbial activity in Saline Soils - SOLANKI, RONISHA B.; ARORA, SANJAY (Journal of Soil and Water Conservation, 2021)
The Litter fall is a very valuable resource. It has important role to play in soil nutrient dynamics, soil properties and energy transfer. Litter fall and decomposition are the two main processes accounting for soil enrichment in agroforestry system. Litter fall in soil has strong bearings in maintenance of hydrological cycles apart from influencing soil properties and ecology. The extent of enrichment in soil properties depends on the tree species, management practices and the quantity and quality of litter. Decomposition of various litter components results in conversion of nutrients and their release depends on litter composition, microbial activity, C:N ratio, temperature, moisture and other factors. It has been reported that 63, 50, 48, 67 and 57% of nutrient uptake returned to soil annually in Dalbergia sisso while 39, 9, 23, 14 and 13 % in Eucalyptus with respect to N, P, K, Ca and Mg, respectively. Litter fall significantly increased the soil microbial populations and the enzymes activities in the normal soil while in the saline or the alkali soils, salt concentration affect activity of microbial population and enzyme activity.